CRSTDLA-ARAFREQ: AN ARABIC LEXICAL DATABASE FOR SPEECH-LANGUAGE ASSESSMENT IN ALGERIAN PRIMARY SCHOOLS - Kahina Lettad; Amina Saadedine; Fouzia Badaoui; Mahdia Benaissa; Radia Baba; Nouara Badi; Ratiba Khorta; Asma Benchouk (International Journal of Innovative Technologies in Social Science, 2026)
Lexical databases are increasingly recognized as indispensable resources for both speech-language pathology and education. This paper presents CRSTDLA-Arafreq, the first Modern Standard Arabic lexical database specifically constructed from Algerian textbooks (Preschool to Grade 3), integrating written and oral frequencies as well as student productions. While such tools enable clinicians to design sensitive assessments and support teachers in selecting age-appropriate materials, Algeria has lacked a reference database tailored to its specific school and clinical contexts.To address this gap, the CRSTDLA-Arafreq project was launched at the Scientific and Technical Research Center for the Development of the Arabic Language. Conducted over three years by a multidisciplinary team, the project provides a robust, evidence-based lexical resource grounded in authentic Algerian primary school corpora to support inclusive education and validated diagnostic instruments.